THE PHILOSOPHY OF DESTRUCTION: “CATECHISM OF A REVOLUTIONARY” IS KILLER-TEXT - Goncharov, Semen A. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2018)
The article presents a philosophical analysis of the “Catechism of a Revolutionary” in the light of its paradoxically and nihilistic boundedness which resulted in the system of practical actions of S. G. Nechaev, led to the murder of student Ivanov. In this connection the identification of the philosophical foundation of the Catechism of a Revolutionary becomes relevant, as well as the definition of its nature in the scale of textuality and effectiveness. The author proposes to consider the “Catechism of a Revolutionary” as a philosophical text on the basis of the presence of metaphysical and existential aspects in the article. At the same time, the author highlights such key features: a focus on practice (rejection of theorizing in favour of the action “here and now”), substitution of purpose by means (replacing the value of the public weal with total destruction and the paradox of the struggle for equality through formation of a rigid hierarchy), as well as extreme ethical nihilism and cynicism. All these premises allow the author to designate the ideological foundation of the “Catechism of a Revolutionary” as a holistic and consistent philosophy of destruction. In addition, this philosophy is considered in the context of its direct embodiment, implemented by S. G. Nechayev: lie, blackmail, compromising, and most importantly – murder. The author of the article concludes that it is impossible to explore the “Catechism of a Revolutionary” apart from the actual consequences of the implementation of his philosophy, and therefore one cannot speak only of his textual nature, detached from the real life. Instead, it should be considered as a fusion of textuality and effectiveness, which directly transforms being and affects people’s lives. Thus, the “Catechism of a Revolutionary” is presented by the author as a killer-text, consisting of a philosophy of destruction on the one hand and its embodiment into reality on the other. Such an approach allows not only to comprehensively explore the nature of the “Catechism of a Revolutionary”, but also to identify a number of dangers that the philosophy of destruction bears inside.